Trade liberalisation and shadow prices in the presence of tariffs and quotas - Neary, J (Blackwell Publishing, 1995)
This paper examines the welfare effects of trade liberalisation and economic growth in an economy which is large enough to influence world prices and in which trade is restricted by both tariffs and quotas. I derive general expressions for shadow prices of goods and foreign exchange and use them to generalise the standard radial reduction and concertina reform results. I also derive a general expression for shadow prices of factors of production and use it to synthesise the classic results of Bhagwati and Johnson on immiserizing growth. Finally, I develop a new geometric technique to illustrate the results.